DEVELOPMENT OF FAST - STRENGTH QUALITIES IN A GYMNAST - Khurozov Gayrat Keldiyorovich (Web of Journals Publishing, 2023)
The article is devoted to the issues of voluntary training of athletes. Concepts of will and volitional actions, volitional qualities, contribution to achieving high results in sports activities.
Keywords: Will, individual mental process, voluntary or volitional action, volitional quality, technical and tactical preparation, activity.